Are Natural Resources Blessing or Curse? : Case Study of Libya - Tsintsadze, Ana; Čermáková, Klára; Kotrba, Vojtěch; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2022)
Significance of the oil prices are demonstrated to the world economy since the 1970s. Libya possesses the largest oil reserves in Africa, making the state one of the leading oil exporters. This study examines whether and to what extent this natural wealth is the source of Libya’s economic growth. Effects of the Second Libyan Civil War, Coronavirus pandemic, and IS terrorist attacks are discussed and analyzed to a macroeconomic extent. Four distinctive regression models are constructed applying the same dependent variable GDPreal, employing the time-series data for the period 2000-2021. The first fundamental model treats oil revenues, prices, and exports as independent variables. It verifies the hypothesis that oil prices positively affect the production of all final goods within the economy. The second and third models investigate the influence of oil on real GDP through electricity production since oil represents the primary source of electricity in Libya. These analyses exhibited the positive impact of electricity on the GDP; Moreover, they emphasize the cruciality of diversification, which is an essential precondition for a stable economy in order to prevent volatility during oil production disruptions that lead to the oil revenue fluctuations. The last, fourth model approaches energy as a whole, as one of the contributors to the goods and services production. This model provided the outcome that is in accordance with the research of Noor and Siddiqi that the energy sector is the backbone of the economy. It indicated that energy consumption is positively related to GDP growth. Since oil is the major source of the energy, it is concluded that possession of oil is vitally important for the economic development of Libya. Ramsey’s RESET and Breusch-Pagan tests were applied with the aim of removing non-linearity and heteroskedasticity.
Empirical analysis reveals that higher oil prices result in a higher gross domestic product; however, oil price decline results in diminished government revenues and subsequently reduced public spending and investments, which eventually leads to economic downfall.
Vedoucí práce: Klára Čermáková
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses